ASSESSMENT OF CORONARY ATHEROSCLEROSIS PROGRESSION IN PATIENTS WITH FIVE YEAR HISTORY OF MYOCARDIAL INFARCTION DEPENDING ON THE STATIN THERAPY COMPLIANCE - A. I. Chesnikova; V. A. Safronenko; A. V. Hripun (Столичная издательская компания, 2015)
Aim. To study the coronary atherosclerosis progression in patients with 5-year history of myocardial infarction (MI) depending on the statin therapy compliance. Material and methods. Patients (n=31) with a five year history of MI were involved into the study. Patients were divided into two groups depending on the statin therapy compliance during 5 years after MI: group 1 - patients with high compliance, group 2 - patients with low compliance. Assessment of the coronary angiography and lipid profile was performed first time in 2005-2006 during hospital treatment for MI and after 5 years again. Results. Increase in the proportion of patients with two and three coronary vessel disease was found after 5 years of observation, despite the high rate of percutaneous coronary intervention (77.4%) and hypolipidemic therapy. Hemodynamically significant restenosis was found in 11.8% (group 1) and 21.4% (group 2) of patients. Target total cholesterol level was reached only in 42.9% and 11.8% of patients in group 1 and 2, respectively. The target level of low density cholesterol was achieved in no one patient. Conclusion. The findings suggest that in patients with 5-year history of MI coronary atherosclerosis progresses regardless of the statin therapy compliance.